2012
DOI: 10.1104/pp.111.192658
|View full text |Cite
|
Sign up to set email alerts
|

Role of cis-12-Oxo-Phytodienoic Acid in Tomato Embryo Development    

Abstract: Oxylipins including jasmonates are signaling compounds in plant growth, development, and responses to biotic and abiotic stresses. In Arabidopsis (Arabidopsis thaliana) most mutants affected in jasmonic acid (JA) biosynthesis and signaling are male sterile, whereas the JA-insensitive tomato (Solanum lycopersicum) mutant jai1 is female sterile. The diminished seed formation in jai1 together with the ovule-specific accumulation of the JA biosynthesis enzyme allene oxide cyclase (AOC), which correlates with eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
67
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 76 publications
0
67
0
2
Order By: Relevance
“…After successful fertilization, NO and JA are likely also important during embryo development (Supplemental Fig. S9; Goetz et al, 2012) and defense (Bosch et al, 2014), as indicated by recent studies in tomato (Solanum lycopersicum). Therefore, it is conceivable that our findings have important implications for other plant species and conditions in which NO and/or JA act as signaling components: in the case of peroxisomal NO during abiotic stress in roots (Corpas et al, 2009;Corpas and Barroso, 2014a) and in the case of JA during herbivory/wounding or plant-pathogen interactions.…”
Section: Discussionmentioning
confidence: 96%
“…After successful fertilization, NO and JA are likely also important during embryo development (Supplemental Fig. S9; Goetz et al, 2012) and defense (Bosch et al, 2014), as indicated by recent studies in tomato (Solanum lycopersicum). Therefore, it is conceivable that our findings have important implications for other plant species and conditions in which NO and/or JA act as signaling components: in the case of peroxisomal NO during abiotic stress in roots (Corpas et al, 2009;Corpas and Barroso, 2014a) and in the case of JA during herbivory/wounding or plant-pathogen interactions.…”
Section: Discussionmentioning
confidence: 96%
“…The above described embryo phenotype of jai1 flowers could be partially rescued by endogenously formed OPDA in repeatedly wounded plants compared with un-wounded plants. 25 All these data suggest a COI1-independent role of seed coat-generated OPDA in embryo development of tomato.…”
mentioning
confidence: 88%
“…Indeed, OPDA was the dominant compound in the seed coat of wild type seed and accumulated in the acx1 seeds. 25 Increased programmed cell death (PCD) monitored by the TUNEL assay was observed in the seed coat and endosperm of spr2 seeds compared with that of wild type seeds. To proof whether OPDA was the essential compound for embryo development, a rescue of the embryo phenotype of spr2 seed was tried by OPDA treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…20 Additionally, seed formation in tomato is regulated by OPDA. 21 Stress responses in JA-deficient but OPDA-containing lower plant species, such as Marchantia polymorpha, 22 Selaginella martensii 23 and Physcomitrella patens, 24 point to a signaling function of OPDA. These data correspond to a proteomic analysis of about 6.000 proteins in A. thaliana showing that nearly 5% of the wound-inducible proteins are synthesized JA-independently, that means they are induced COI1-independently.…”
mentioning
confidence: 99%